Analysis Of Ketone Formation In The Urine Of Futsal Players Following A Simulated Match Using Ketostix - Wahid, Wahyana Mujari; Arimbi; Arifuddin Usman; Rusli; Poppy Elisano Arfanda (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
High-intensity physical activity such as futsal predominantly relies on the anaerobic energy system and has the potential to trigger the formation of ketone bodies as an alternative energy source. While studies on ketones often focus on fasting, ketogenic diets, or metabolic diseases, research on ketone formation due to intense physical activity remains limited. This study aimed to analyze the formation of urinary ketones in futsal players following a simulated match and to assess the distribution of ketone levels produced. This descriptive observational study involved 22 male futsal players aged 18–25 years. Subjects underwent a simulated futsal match (2 × 20 minutes with a 10-minute halftime break). Urine samples were collected approximately 10 minutes post-match and analyzed using Ketostix to detect urinary ketone levels, classified as negative, mild, moderate, or high. All players tested positive for urinary ketones. A total of 90.9% exhibited mild ketonuria (0.5 mmol/L), 9.1% showed moderate ketonuria (1.0 mmol/L), and no cases of severe ketonuria were observed. These findings indicate that high-intensity futsal activity is sufficient to induce metabolic changes leading to ketogenesis. High-intensity futsal activity can stimulate endogenous ketone production as a response to glycogen depletion. Monitoring ketone levels may serve as an important indicator in designing training, recovery, and nutritional strategies in high-intensity sports. Further studies are recommended to explore the relationship between ketone levels, athletic performance, and metabolic risk in athletes.